Sitting: Maschke, Breitscheid, Juchacz, Bohm-Schuch. Standing: Crispien, Krüger, Mozes, Stahl, Künstler, Wels
Sitting: Maschke, Breitscheid, Juchacz, Bohm-Schuch. Standing: Crispien, Krüger, Mozes, Stahl, Künstler, Wels.